Trade cooperation between Kazakhstan and Germany - Buchmann, K.; Assanova, M.K.; Mussina, S.T. (BUKETOV BUSINESS REVIEW, 2018)
The article discusses trade cooperation between Kazakhstan and Germany. It includes trade cooperation, economic policy cooperation, economic relationship between Kazakhstan and Germany, the industrial production of Kazakhstan, foreign trade between Kazakhstan and Germanyand so on. Doubtless, Germany and Kazakhstan have maintained diplomatic relations, bilateral contracts have developed dynamically. Both countries are members of the Organization for Security and Cooperation in Europe (OSCE), Kazakhstan is a member of the NATO Partnership for Peace. Kazakhstan is also beyond the economic relations a friend and important partner for Germany. Furthermore, the economic relations between Kazakhstan and Germany will continue to develop in the same way, a promising future awaits the cooperation. The concept of trade cooperation is explained. Kazakhstan and Germany are described as trading partners. The article describes the development of relations between Kazakhstan and Germany, lists international agreements signed between the two countries. Particular attention is paid to the activities of the Kazakh-German Intergovernmental Working Group on trade and business operation of German-Kazakhstan Economic Council on Strategic Cooperation. The article is about the activity of the Association of German Business in the Republic of Kazakhstan. Specified role in the development of relations and establishment of business contacts between the two countries Training Program Manager, which since 2004 in Germany were trained 573 managers from Kazakhstan. The article analyzes the dynamics of trade indicators of Kazakhstan and Germany, certain groups of goods in exports and imports, the share of trade with other countries.